Consumer Policy in Poland in the Period of Transformation - Malczyńska-Biały, Mira (Studia Historiae Oeconomicae, 2017)
The article is based on an analysis of Polish and international legal acts, government programs and literature, and aims at presenting the concept and the scope of consumer policy in the period of systemic transformation in Poland. The publication features an analysis of the major factors shaping consumer policy in Poland in the years 1989-2004. Selected international legal acts affecting consumer protection in the years 1989-1997 were also analyzed. Elements of consumer policy present in selected governmental economic programs in the period of transformation were synthesized. It was assumed that consumer policy in the period of systemic transformation indirectly resulted from the economic policy of the government. Its shape was primarily affected by the social and economic transformation occurring since 1989 and the birth of free-market economy. The process of adjusting the Polish legislation to the European Union standards, which began in 1991, and subsequent accession to the European Union in 2004 also played an important role.